Research on Equivalent Circuit Model of HVDC Valve and Calculation of Thyristor Junction Temperature - Wei Yao; Yang Liu; Lei Guo; Guojun Ding; Chaofeng Zhang; Sen Wang (Active and Passive Electronic Components)
For the difference of thyristor junction temperature at all levels in the transducer valve assembly in the series water circuit, an equivalent model of thyristor junction temperature calculation for the valve assembly is established, and PLECS simulation software is used to simulate and solve the junction temperature at all levels of the thyristor and check the junction temperature of the thyristor from the highest temperature of the measured radiator surface, and the results of the junction temperature checking show that the equivalent model of thyristor junction temperature calculation for the valve assembly has a high accuracy.